Connecting indigenous peoples mobile phone experiences of three indigenous people groups in the Philippines - Portus, Lourdes M. (2007)
The indigenous peoples (IPs) of the Philippines, numbering between 4.5 million to 10 million, live in mostly remote rural areas, and are generally regarded as marginalized owing to their geographic, economic, social, and political location. Their situation not withstanding, this study shows that selected groups of IPs, the Sama-Tausugs, Aytas, and Dumagats - are no strangers to information and communication technologies, particularly the mobile phone. Their perceptions of the mobile phones are shaped by their present life world. But despite limited financial resources, low literacy level, and poor signal in their respective areas, the IPs have devised ways of acquiring and using the mobile phone to keep them connected to each other and to the "lowlanders." For the IPs of this study, mobile phone ownership and use have provided them access to and acceptance in the mainstream society.
Includes bibliographical references (pages 73-74).
Keywords: Aetas (Philippine People).; Cell phones -- Social aspects